2015
DOI: 10.1016/j.drugalcdep.2015.07.014
|View full text |Cite
|
Sign up to set email alerts
|

The remote brief intervention and referral to treatment model: Development, functionality, acceptability, and feasibility

Abstract: Background Screening, brief intervention, and referral to treatment (SBIRT) is effective for reducing risky alcohol use across a variety of medical settings. However, most programs have been unsustainable because of cost and time demands. Telehealth may alleviate on-site clinician burden. This exploratory study examines the feasibility of a new Remote Brief Intervention and Referral to Treatment (R-BIRT) model. Methods Eligible emergency department (ED) patients were enrolled into one of five models. (1) War… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…An area of focus for practice will be to train clinicians in the use of SBIRT online while identifying additional avenues for universal implementation, perhaps through the use of social media. Boudreaux et al ( 2015 ) demonstrated the potential in such practice. In addition, as has been suggested by Goodwin et al ( 2018 ) previously, public health officials and clinicians might consider creating anxiety-mediating interventions that target social media users during times of crises, such as the COVID-19 pandemic, in an effort to curtail the spread of emotional contagion and/or to promote healthy coping among social media users.…”
Section: Implications For Practicementioning
confidence: 99%
“…An area of focus for practice will be to train clinicians in the use of SBIRT online while identifying additional avenues for universal implementation, perhaps through the use of social media. Boudreaux et al ( 2015 ) demonstrated the potential in such practice. In addition, as has been suggested by Goodwin et al ( 2018 ) previously, public health officials and clinicians might consider creating anxiety-mediating interventions that target social media users during times of crises, such as the COVID-19 pandemic, in an effort to curtail the spread of emotional contagion and/or to promote healthy coping among social media users.…”
Section: Implications For Practicementioning
confidence: 99%
“…Different communication and service delivery strategies should be investigated in team‐based SBIRT models in order to find the most successful workflows. In addition, there may be opportunities to reach out to patients after their visits to conduct SBIRT using technology or phone‐based models, rather than conducting SBIRT during the patient visit . Future research should examine whether clinical setting and workflow adaptations increase implementation success.…”
Section: Discussionmentioning
confidence: 99%
“…The initial online questionnaire was developed by researchers in health care and nursing informatics ( Table 1). 2,[7][8][9][10][11][12][13][14] It included 2 questions about which departments would use the robots and 38 on essential features of the teleconsultation robot.…”
Section: Quantitative Datamentioning
confidence: 99%